105 PET-CT findings in HIV-positive and negative patients with locally advanced cervical cancer in a south african cohort. (18th September 2019) - Simonds, H; Botha, H; Ellmann, A; Warwick, J; Doruyter, A; Van der Merwe, H; Jacobson, J
Abstract : Objectives: PET-CT imaging is commonly used as a staging tool to identify nodal involvement in locally advanced cervical carcinoma (LACC). The value of PET-CT for staging HIV-infected patients with locally advanced CC has not been previously described. We analyzed PET-CT findings in a cohort of patients with LACC in Cape Town, SA. Methods: Patients with LACC FIGO Stage IIb or IIIB, and were referred, on the basis of stage and the availability of bookings, for PET-CT/radiotherapy planning CT from January 2015 to December 2018. A team of expert nuclear medicine physicians and radiologists reported the PET-CT examinations. Descriptive statistics and chi-squared tests were used to compare patients with and without HIV. Results: A total of 286 patients underwent PET-CT. Eighty-nine patients (31.2%) were HIV-positive. Pelvic nodal involvement was notably found in 205 patients (72.4%), including 77.3% of those who had HIV and 70.3% of those who did not (p=0.22); para-aortic nodal disease in 114 patients (42.7% of HIV+ vs 38.8% HIV-, p=0.53); and distant disease in 55 patients (23.6% of HIV+ vs 17.3% HIV-; p=0.22). In total, 223 patients (79.3%), including 81.8% of patients without and 75.0% of patients with HIV (p=0.31), were prescribed standard fractionation EBRT. Twenty-two patients (7.8%) were prescribed hypofractionated EBRT, and 36 patients (12.8%) palliative therapy. Five patients (1.7%) did not return. Conclusions: PET-CT imaging found no differences between LACC patients, with and without HIV, in nodal involvement or occult metastases and did not lead to, or justify, treatment differences.